Changes in the Proportion of Gastrointestinal Emergency Endoscopy and Peptic Ulcer Disease During the COVID-19 Pandemic: A Local Retrospective Observational Study From Vietnam - Dao, Hang Viet; Hoang, Long Bao; Le, Nha Ngoc Hoa; Tran, Trang Thi Thu; Nguyen, Hung Manh; Dao, Long Van; Le, Ngoan Tran (Frontiers in Public Health, 2022)
Objectives: The COVID-19 pandemic has disrupted the practice of gastrointestinal (GI) endoscopy units and may increase the risk of digestive disorders. We describe the situational changes in GI endoscopy and peptic ulcer diseases (PUD) proportion during COVID-19 in Vietnam and examine associated factors. Methods: A retrospective ecological study was conducted on data of Hanoi Medical University Hospital, Vietnam. The number of upper GI endoscopy and the proportion of GI emergency endoscopy and PUD were compared between 2019 and 2020 by month (January to June). Log-binomial regression was used to explore associated factors of GI emergency endoscopy and PUD. Results: The number of endoscopies decreased remarkably during the nationwide social distancing in April 2020. Compared to April 2019, the proportion in April 2020 of both GI emergency endoscopy (4.1% vs. 9.8%, proportion ratio (PR) 2.39, 95% confidence interval (95%CI) 2.00, 2.87) and PUD (13.9% vs. 15.8%, PR 1.14, 95%CI 1.01, 1.29) was significantly higher. In log-binomial models, the proportion of GI emergency endoscopy was higher in April 2020 compared to April 2019 (adjusted PR 2.41, 95%CI 2.01, 2.88). Male sex and age of ≥50 years were associated with increased PUD and GI emergency conditions. Conclusion: We observed the proportion of both GI emergency endoscopy and PUD was significantly higher during the time of the state of emergency due to the ongoing COVID-19 pandemic in 2020 when compared to 2019 at the same health facility in Vietnam. The findings suggest that healthcare delivery reforms during the era of an emerging pandemic are required to reduce digestive disorders in particular and chronic diseases in general.